The impact of technology on the Starbucks experience. Issue 1 (10th April 2023) - Akcam, Bahadir K
This case explores the impact of technology on the consumer experience at Starbucks. It starts with an inquiry about why consumers choose Starbucks stores, even when traveling abroad. Consumer experience is a critical strategic goal for the company, and technology has become a driving force in enhancing it. Starbucks uses technologies such as the Starbucks Mobile App, associated rewards and card systems, internet of things enabled machines in the stores, blockchain technologies connecting stakeholders, and reinforcement learning technology to analyze all the data. Students study the role of these technologies in customer experience and explore different order processes.